1997
DOI: 10.1074/jbc.272.51.32628
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Distribution and Modulatory Role of the γ Subunit of the Na,K-ATPase

Abstract: The Na,K-ATPase comprises a catalytic ␣ subunit and a glycosylated ␤ subunit. Another membrane polypeptide, ␥, first described by Forbush et al. (Forbush, B., III, Kaplan, J. H., and Hoffman, J. F. (1978) Biochemistry 17, 3667-3676) associates with ␣ and ␤ in purified kidney enzyme preparations. In this study, we have used a polyclonal anti-␥ antiserum to define the tissue specificity and topology of ␥ and to address the question of whether ␥ has a functional role. The trypsin sensitivity of the amino terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
133
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 38 publications
(39 reference statements)
6
133
0
2
Order By: Relevance
“…In the present paper, we provide evidence that PLM may be a tissue-specific regulator of NKA similar to other members of the FXYD protein family such as the ␥ subunit of NKA (14,35,36), CHIF (12), and FXYD7 (44). Indeed, our results show that PLM is associated with NKA in heart and skeletal muscles and that it Fig.…”
Section: Discussionmentioning
confidence: 54%
“…In the present paper, we provide evidence that PLM may be a tissue-specific regulator of NKA similar to other members of the FXYD protein family such as the ␥ subunit of NKA (14,35,36), CHIF (12), and FXYD7 (44). Indeed, our results show that PLM is associated with NKA in heart and skeletal muscles and that it Fig.…”
Section: Discussionmentioning
confidence: 54%
“…3 and 5 show definitively that the ␥ modulator is a constituent component in the progenitor cells, and more importantly in mature human erythrocytes. By using the same antibody (B-Ab) in a much higher titer than used previously (13) in a study where the ␥ modulator was not detected, it was now clearly found (Fig. 5).…”
Section: Discussionmentioning
confidence: 91%
“…The basis for this difference in isoform expression between sheep and humans is unknown. The ␥ modulator of the Na pump (2,6,12) has not been found in rat red cells (13), but the evidence presented below clearly documents, by both Northern and Western blot analyses, that the ␥ modulator is a normal constituent of precursor as well as mature human red blood cells. We have changed the notation to refer to the ␥ component as the ␥ modulator or FXYD2 rather than the ␥ subunit; a change that is consistent with its evident function as a member of the FXYD family (14).…”
mentioning
confidence: 98%
“…1) Stable transfection of ␥ in NRK-52E cells, which do not express ␥ under normal conditions, results in a significant delay of cell growth compared with non-transfected cells (8,20). 2) While being exclusively expressed in kidney, expression of ␥ is normally absent in renal cells in culture (20,21) but can be induced with genotoxic stress (hypertonicity (22,25), heat shock, oxidative stress, and treatment with heavy metals). As we showed here, induction of endogenous ␥a in NRK-52E treated with hypertonicity correlated with significant reduction in the V max of the pump and was accompanied by a reduction in the rate of cell division.…”
Section: Discussionmentioning
confidence: 99%